Preoperative Concentrated Urine Increases the Incidence of Plasma Creatinine Elevation After Major Surgery - Engel, Dominique; Löffel, Lukas M.; Wuethrich, Patrick Y.; Hahn, Robert G. (Frontiers in Medicine, 2021)
Background: Postoperative elevation of plasma creatinine is a frequent complication to major surgery. A rise by 50% fulfills the criterion for Acute Kidney Injury. We studied the relationship between concentrated urine before surgery, which is usually a sign of chronically low intake of water, and the perioperative change in plasma creatinine. Methods: The creatinine concentration was measured in plasma and urine just before and at 6 h, 1 day, and 2 days after major abdominal surgery in a consecutive series of 181 patients. Receiver operating curve analysis was used to find the optimal cut-off to separate concentrated from diluted urine. Results: Urine creatinine of 11.3 mmol/L before the surgery started was exceeded in one third of the patients and associated with greater increase in plasma creatinine at 6 h (median 21 vs. 10%) and at 1 day postoperatively (21 vs. 7%; P < 0.0001). Elevation of plasma creatinine of >25% occurred in 41% and 19% in those with high and low urine creatinine, respectively (P < 0.001) and an increase by >50% in 16% and 10% (P = 0.27). Patients with high urine creatinine before surgery failed to further concentrate their urine during the perioperative period, which is normally associated with intensified renal fluid conservation. Conclusion: High urinary concentration of creatinine before surgery should be considered as a risk factor for postoperative elevation of plasma creatinine. The mechanism is probably that the renal threshold is then more easily reached.